Evaluation of the rural response system intervention to prevent violence against women: findings from a community-randomised controlled trial in the Central Region of Ghana - Alangea, D.O.; Addo-Lartey, A.A.; Chirwa, E.D.; Sikweyiya, Y.; Coker-Appiah, D.; Jewkes, R.; Adanu, R.M.K. (Global Health Action, 2020)
Background: Intimate partner violence (IPV) affects one in three women globally and undermines women’s human rights, social and economic development, and health, hence the need for integrated interventions involving communities in its prevention. Objective: This community-randomised controlled trial evaluated the Rural Response System (RRS) intervention, which uses Community Based Action Teams to prevent IPV by raising awareness and supporting survivors, compared to no intervention. Methods: Two districts of the Central Region of Ghana were randomly allocated to each arm. Data were collected by repeated, randomly sampled, household surveys, conducted at baseline (2000 women, 2126 men) and 24 months later (2198 women, 2328 men). The analysis used a difference in difference (DID) approach, adjusted for age and exposure to violence in childhood. Results: In intervention communities, women’s past year experience of sexual IPV reduced from 17.1% to 7.7% versus 9.3% to 8.0% in the control communities (DID = −9.3(95%CI; −17.5,−1.0), p = 0.030). The prevalence of past-year physical IPV among women in the intervention communities reduced from 16.5% to 8.3% versus 14.6% to 10.9% in the controls (DID = −4.2(−12,3.6), p = 0.289). The prevalence of severe IPV experienced by women reduced from 21.2% to 11.6% in intervention versus 17.3% to 11.4% in controls (DID = −3.7(−12.5,5.1), p = 0.408). The direction of impact of the intervention on violence perpetrated by men was more towards a reduction but changes were not statistically significant. Emotional IPV perpetration was significantly lower (DID = −15.0(−28.5, −1.7), p = 0.031). Women’s depression scores and reports of male partner controlling behaviour significantly also reduced in the intervention arm compared to those in the control arm (DID = −4.8(−8.0,−1.5), p = 0.005; DID = −2.7(−3.3,−1.0), p = 0.002, respectively). Conclusion: Our findings indicate that the RRS intervention reduced women’s experiences of IPV, depression, and partner controlling behaviour and some evidence of men’s reported reductions in the perpetration of IPV. The RRS intervention warrants careful scale-up in Ghana and further research.
Research Article
Keywords: Intimate partner violence; violence against women; randomised control trial; community intervention; the rural response system; Ghana